2022
DOI: 10.1002/vms3.951
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence ofTrichinellain pigs: A systematic review and meta‐analysis

Abstract: Background: Investigating the global epidemiological patterns of Trichinella in pigs is required for accurate recognition and to establishing proper control programmes and preventive measures, as well as to decrease human exposure. Objectives: To obtain a better understanding of the global prevalence of Trichinella in domestic pigs and factors that might influence the prevalence, a systematic review and meta-analysis was performed. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…In Europe, cross-sectional serological studies in pigs have been carried out only in Croatia (Marinculic et al, 2001), with a described seroprevalence of 5.5% (n = 475), Netherlands (Van der Giessen et al, 2007) with 0.24% (n = 845) and Estonia (Karssin et al, 2016), with no positive sera found (n = 374). Eslahi et al (2022) performed a systematic review and meta-analysis on the global prevalence of trichinellosis in domestic pigs, analysing 21 cross-sectional studies in pigs from 17 different countries: pooled seroprevalence was 4.3% (95% CI: 1.1%-9.4%), ranging from 0% in Colombia (Pulido-Villamarín et al, 2019) and Korea (Kim et al, 2015) to 13.4% (25/186) in Nigeria (Ojodale et al, 2015). Since the extensive farming system in which Iberian pigs are raised allowed coexistence of pigs and wild boar in the same habit, transmission from wild boar to Iberian pigs could be possible, as suggested by Papatsiros et al (2020) from their study in Greece and by Kärssin et al (2021), analysing wild and game animals in Estonia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Europe, cross-sectional serological studies in pigs have been carried out only in Croatia (Marinculic et al, 2001), with a described seroprevalence of 5.5% (n = 475), Netherlands (Van der Giessen et al, 2007) with 0.24% (n = 845) and Estonia (Karssin et al, 2016), with no positive sera found (n = 374). Eslahi et al (2022) performed a systematic review and meta-analysis on the global prevalence of trichinellosis in domestic pigs, analysing 21 cross-sectional studies in pigs from 17 different countries: pooled seroprevalence was 4.3% (95% CI: 1.1%-9.4%), ranging from 0% in Colombia (Pulido-Villamarín et al, 2019) and Korea (Kim et al, 2015) to 13.4% (25/186) in Nigeria (Ojodale et al, 2015). Since the extensive farming system in which Iberian pigs are raised allowed coexistence of pigs and wild boar in the same habit, transmission from wild boar to Iberian pigs could be possible, as suggested by Papatsiros et al (2020) from their study in Greece and by Kärssin et al (2021), analysing wild and game animals in Estonia.…”
Section: Discussionmentioning
confidence: 99%
“…Both domestic and wild Suidae are the primary source of Trichinella sp. infection in humans worldwide (Eslahi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations